Effects of 28Si ions, 56Fe ions, and protons on the induction of murine acute myeloid leukemia and hepatocellular carcinoma - Weil, Michael M., author; Ullrich, Robert L., author; Fallgren, Christina M., author; McCarthy, Maureen, author; Yu, Yongjia, author; Genik, Paula C., author; Ray, F. Andrew, author; Public Library of Science, publisher (Colorado State University. Libraries, 2014)
Estimates of cancer risks posed to space-flight crews by exposure to high atomic number, high-energy (HZE) ions are subject to considerable uncertainty because epidemiological data do not exist for human populations exposed to similar radiation qualities. We assessed the carcinogenic effects of 300 MeV/n 28Si or 600 MeV/n 56Fe ions in a mouse model for radiation-induced acute myeloid leukemia and hepatocellular carcinoma. C3H/HeNCrl mice were irradiated with 0.1, 0.2, 0.4, or 1 Gy of 300 MeV/n 28Si ions, 600 MeV/n 56Fe ions or 1 or 2 Gy of protons simulating the 1972 solar particle event (1972SPE) at the NASA Space Radiation Laboratory. Additional mice were irradiated with 137Cs gamma rays at doses of 1, 2, or 3 Gy. All groups were followed until they were moribund or reached 800 days of age. We found that 28Si or 56Fe ions do not appear to be substantially more effective than gamma rays for the induction of acute myeloid leukemia. However, 28Si or 56Fe ion irradiated mice had a much higher incidence of hepatocellular carcinoma than gamma ray irradiated or proton irradiated mice. These data demonstrate a clear difference in the effects of these HZE ions on the induction of leukemia compared to solid tumors, suggesting potentially different mechanisms of tumorigenesis. Also seen in this study was an increase in metastatic hepatocellular carcinoma in the 28Si and 56Fe ion irradiated mice compared with those exposed to gamma rays or 1972SPE protons, a finding with important implications for setting radiation exposure limits for space-flight crew members.
Keywords: high LET ions; leukemia; HZE ions; space radiation; epithelial cancer; relative biological effectiveness; risk assessment